Timed compiled-code functional simulation of embedded software for performance analysis of SOC design. - Jong-Yeol Lee
A new timing generation method is proposed for the performance analysis of embedded software. The time stamp generation of input/output (I/O) accesses is crucial to performance estimation and architecture exploration in the timed functional simulation that simulates the whole design at a functional level with timing. A portable compiler is modified to generate time deltas which are the estimated cycle counts between two adjacent I/O accesses by counting the cycles of the intermediate representation (IR) operations and using a machine description that contains information on a target processor. Since the proposed method is based on the machine-independent IR of a compiler, the method can be applied to various processors by changing the machine description. The experimental results show that the proposed method is effective in that the average estimation error is about 2% and the maximum speed-up over the corresponding instruction-set simulators is about 300 times. The proposed method is also verified in a timed functional simulation environment.
Keywords: SOC design; Compiled-code functional simulation; Embedded software; Input/output access; Intermediate representation operation; Performance analysis; Portable compiler; Timing generation